Avaliação do uso do etanol e do isopropanol como alternativa ao n-hexano na extração do óleo de café verde (Coffea arabica) em banho ultrassônico e caracterização dos extratos obtidos - Carbonar, Henrique Larocca (2022)
This study proposed the total or partial replacement of n-hexane by isopropanol or ethanol in the ultrasound-assisted extraction of green coffee (Coffea arabica) oil. The kinetic curve of the extraction process was determined to define the time needed to reach saturation, establishing the time of 120 minutes as the ideal for this process. The yields of the oil extracted with the pure solvents and the mixture of n-hexane with the other two solvents in different proportions were quantified. The samples obtained were analyzed through Gas Chromatography to determine the fatty acids constituting the green coffee oil and their concentrations, correlating the change in the solvent used with changes in these factors. In addition, coffee oil samples were analyzed by Fourier transform infrared spectroscopy (attenuated total reflectance mode) to observe the functional groups that characterize the extracts, followed by the determination of the principal components. The results showed that the concentration of fatty acids does not undergo significant changes with the replacement of n-hexane by isopropanol or ethanol or by their mixture, and it was also observed that the use of a mixture of isopropanol and n-hexane allowed the extraction of an oil with a higher concentration of polyunsaturated fatty acids of commercial and nutritional interest. Regarding the oil content obtained, it was found that the yield did not vary significantly with the change of solvent. No significant changes in functional groups were observed with changes in solvents, and these results were confirmed by the principal components analysis, where only one of the components explained the small changes. Thus, there are indications of the feasibility of using isopropanol and ethanol in the extraction process of green coffee oil assisted by an ultrasonic bath, thus allowing an extraction without or with a smaller amount of the toxic solvent n- hexane.